Tri Hita Karana Memoderasi Partisipasi Penyusunan Anggaran, Asimetri Informasi, dan Komitmen Organisasi terhadap Sennjangan Anggaran - Diviariesty, Kadek; Asri Dwija Putri, IGAM (E-Jurnal Akuntansi; Vol 31 No 1 (2021)DO - 10.24843/EJA.2021.v31.i01.p03, 2021)
This study aims to determine the effect of budgetary participation, information asymmetry and organizational commitment to budgetary slack with the Tri Hita Karana culture as a moderating variable. The analysis technique used is Moderated Regression Analysis. The results showed that budgetary participation and organizational commitment had no significant effect on budgetary slack. Information asymmetry has a positive effect on budgetary slack. The interaction between budgeting participation and the Tri Hita Karana culture is unable to moderate budgetary participation against budgetary slack. The interaction of information asymmetry with the Tri Hita Karana culture is able to weaken the positive influence of information asymmetry on budgetary slack. The interaction between organizational commitment and the Tri Hita Karana culture is unable to moderate organizational commitment to budgetary slack. Keywords: Tri Hita Karana; Budgetary Participation; Information Asymmetry; Organizational Commitment; Budgetary Slack.